Subject Clauses in Old English: Do They Really Exist? - Belén Méndez Naya (Miscelánea: A Journal of English and American Studies)
Recently, the existence of subject clauses in Old English has been denied mainly because clauses do not occur in sentence initial position. This paper argues that the alternative analyses put forward in the literature fail to account for the linguistic data and that occurence in initial position is not a relevant criterion for subjects at this early stage in the development of English.